Conversion of Thesis to Peer-Reviewed Publication - Dhaval Shukla; Manjul Tripathi; Bhagavatula Indira Devi (Indian Journal of Neurosurgery)
Introduction Writing a thesis or dissertation during a postgraduate medical or surgical training is a part of curriculum, which is considered a major component of training during residency. We aimed to analyze and find out the fate of thesis of our residents, their outcome, and impact. We have also evaluated the reasons for not publishing the thesis in a peer-reviewed paper. Methods This study was conducted at a neurosurgical department of a premier training institute. PubMed and Google Scholar were searched for the topics of thesis and names of residents to find out whether any paper was published similar to topic of thesis. The faculties and residents were also personally contacted to evaluate the publication status of their thesis. A questionnaire was sent to the students who did not publish their thesis to find out the reasons for not submitting for publication. Results Total 56 residents submitted 85 thesis. The conversion rate to peer-reviewed publication was 32.5%. There was decreasing trend of conversion to publication over 10 years. The most common reasons for not publishing was a bad design of study, or deemed worthless for publication. Conclusion Conversion rate of thesis to paper is poor. In addition to writing thesis, candidates should be encouraged to have publications in indexed journal as full-length articles. Such publications carry more significance in long-term career of a resident.